Na⁺ transport and structural evolution in NaTFSI-Doped PMMA gel polymer electrolytes - Nurfatin Nabilah, Abdul Hafidz; Norfatihah, Mazuki; Nuraziliana, Muhd Ghazali; Mohd Zieauddin, Kufian; Ahmad Salihin, Samsudin (Springer Berlin Heidelberg, 2026)
In this work, poly(methyl methacrylate) (PMMA) was incorporated with sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) and processed under vacuum to form GPE membranes. Structural interactions between Na⁺ ions and the PMMA host were confirmed by Fourier transform infrared (FTIR) analysis, while differential scanning calorimetry (DSC) showed a noticeable reduction in both the glass transition and crystallization temperatures, indicating enhanced chain flexibility and reduced crystallinity. Electrochemical impedance spectroscopy revealed that the sample with 20 wt% NaTFSI exhibited the highest ionic conductivity, reaching 3.65 × 10⁻⁴ S cm⁻¹ at room temperature. Additionally, a sodium-ion transference number of 0.50 was recorded, indicating selective and efficient Na⁺ transport through the polymer matrix. These results highlight the suitability of NaTFSI-doped PMMA GPEs for advanced sodium-ion devices where ionic mobility and polymer dynamics are crucial for performance.